Commentary on the Basis of the Instrumental Initiation of Fiscal Penal Proceedings and the Right to Court of the Resolution of the Supreme Administrative Court I Fps 1/21 – Judicial Control - Szymacha, Adam; Rogalski, Kamil (Journal of Finance and Financial Law, 2021)
The purpose of the article/hypothesis: The presented article focuses on a new resolution of the Supreme Administrative Court I FPS 1/21. In this resolution an assessment of instrumental initiation of criminal fiscal proceedings in order to suspend the running of the limitation period of a tax liability has been undertaken. The Supreme Administrative Court assessed that administrative courts have the right to examine the legitimacy of initiation of such proceedings. This position is important insofar as it also touches upon the issue of the right to a fair trial, as well as the right to property and legal certainty. The main aim of this article is to check the impact of this resolution on described fundamental rights. Methodology: This article will use the comparative law method. Especially the case law of different courts will be shown. The dogmatic-legal method will also be used as an auxiliary. Results of the research: This resolution is crucial for the fundamental right for fail trial. It has also impact on the right to property and principle of legal certainity. It may also be some element that strengthens the rule of law.